Chu tan shen du xue xi : shi yong TensorFlow = TensorFlow for deep learning : from linear regression to reinforcement learning - Ramsundar, Bharath; Bosagh Zadeh, Reza (GoTop Information, Inc., 2018)
Detailed summary in vernacular field.